IN SITU MASS SPECTROMETERS FOR APPLICATIONS IN SPACE. Issue 5 (19th September 2020) - Vazquez, Timothy; Vuppala, Sinduri; Ayodeji, Ifeoluwa; Song, Linxia; Grimes, Nathan; Evans‐Nguyen, Theresa
Abstract : Mass spectrometry (MS) has played a remarkable role in exploring the chemical make‐up of our solar system. In situ probes were historically developed to analyze inorganic/elemental compositions while leveraging native ions or harsh ionization methods to aid in exploring astrophysics applications (e.g., heliophysics). The part played by MS is demonstrated in a majority of scientific payloads focused on exploration, particularly at the turn of the century with missions including Cassini‐Huygens, Rosetta, and now Mars Science Laboratory. Plasma mass spectrometers have grown more sophisticated to interrogate fundamental inorganic analysis (e.g., solar wind and magnetospheres) including both native ions and neutrals. Cosmic dust floating in‐between and orbiting planetary bodies has been targeted by unique sampling via impact ionization. More complex systems rely on landed planetary instrumentation with lessons learned from pioneering missions in the 1970s and 1980s to near neighbors Mars and Venus. Modern probes have expanded applicable target chemicals by recognizing the needs to provide for molecular analyses, extended mass range, and high resolution to provide unequivocal detection and identification. Notably, as the field surrounding astrobiology has gained momentum, so has the in situ detection of complex molecular chemistry including the chemical evolution of organic molecules. Mission context often includes long term timelines from spacecraft launch to arrival and additionally the diverse target environments across various planets. Therefore, customized experimental designs for space MS have been born of necessity. To this point, the development of MS instrumentation on Earth has now far outpaced development for experiments in space. Therefore, exciting developments lie ahead among various international space agencies conducting current and future mission planning with increasingly enhanced instrumentation. For instance, near‐neighbor Mars has entertained considerable attention with complex MS instrumentation with laser desorption ionization aboard the Mars Organic Molecule Analyzer instrument. To study comets, the Rosetta mission employs a secondary ionization mechanism. Meanwhile, the various moons of Jupiter and Saturn have intriguing surface and subsurface properties that warrant more advanced analyzer systems. Instrumentation design will continue to evolve as requirements develop and this review serves as a reflection of the contribution of in situ MS to space exploration in the past 20 years and the anticipated contribution yet to come. © 2020 John Wiley & Sons Ltd. Mass Spec Rev